Classification and Function of Motifs in “5 Dongeng Anak Dunia” Based on Thompson's Theory - Aura Zahra Amin; Afni Apriliyanti Devita (EDU-KATA, 2026)
Children's literature plays an important role in shaping meaningful reading experiences through simple stories. One of the intrinsic elements that plays a role in building story continuity and conveying meaning is motif. Motif is a narrative element that appears repeatedly in a story and serves to strengthen the structure and meaning of the story. This study aims to identify the motifs found in the book 5 Dongeng Anak Dunia by Dedik Dwi Prihatmoko and analyse the role of these motifs in constructing the plot and meaning of the stories. This study uses a descriptive qualitative approach with Stith Thompson's motif theory as the main theory. The research data consists of words, phrases, and events in five fairy tales that indicate the emergence of motifs. Data collection techniques were carried out through intensive reading and data recording, while data analysis was carried out by classifying motifs based on Thompson's motif categories and examining their functions in the story structure. The results show that motifs such as honesty, sacrifice, kindness, and courage appear repeatedly and function as plot drivers as well as a means of conveying moral values. These motifs help build the unity of the story and reinforce the meaning conveyed to child readers. Thus, this study confirms that motifs play an important role in creating a complete and meaningful reading experience in children's literature.